The Jeme Semende: From Pasemah To The Land of Sang Bumi Ruwa Jurai (The Cultural Identity Study Of Semende Diaspora) - Maskota Delfi; Yetty Oktayanty; Johan Richard Weintré; Afrida Afrida; Afrida Afrida (Universitas Andalas, 2023)
Ethnic diversity is one of the outstanding characteristics of Indonesian culture. Diversity creates potential challenges and opportunities in the multi-cultural ethnic relations, with positive and negative social capital forming among ethnic groups. The ethnic cultural claim is principally pronounced with the kingship ties that bind the family in the Semende people. They are depicted by the unique Tunggu Tubang family tie system, in which normally the eldest female sibling in a family becomes the main guardian of all family members when the parents have become less able to manage the family house, yard, family agricultural fields, gardens and foremost the caring of brothers and sisters if in need. This paper is based on the research in the geographical location of the Tanjung Raja district in North Lampung, where one of the sub-districts is inhabited by the Semende people. This study used an ethnographic approach with participatory observation techniques and in-depth interviews of key informants. This research explores the cultural identity of the Jeme Semende diaspora by reconnoitering the knowledge of the actors of what and how these cultural customs are understood and applied in daily life. The research conclusion indicates that the Jeme Semende's cultural identity is maintained despite being surrounded by other ethnic groups in Tanjung Raja. And how